2004
DOI: 10.1080/00365520410003524
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer incidence and mortality in patients with long-segment Barrett's Oesophagus after a mean follow-up of 12.7 years

Abstract: The annual risk of developing HGD or adenocarcinoma in patients with long-segment BO is 0.83%. Death due to adenocarcinoma is, however, uncommon, even in a cohort of patients with long-segment BO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 14 publications
2
80
0
1
Order By: Relevance
“…LOH was discriminated for all BE specimens combined at t 5 2 of 5q in 0%, 9p in 56%, 17p in 44% and 18q in 20% of informative cases. The LOH patterns of the BE's at t 5 0 (14 MET, 4 LGD, 3 HGD), t 5 1 (18 MET, 3 LGD) and t 5 2 (8 MET, 2 LGD) were not statistically different (Fig. 2b), despite histologic downgrading of dysplasia after therapy.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…LOH was discriminated for all BE specimens combined at t 5 2 of 5q in 0%, 9p in 56%, 17p in 44% and 18q in 20% of informative cases. The LOH patterns of the BE's at t 5 0 (14 MET, 4 LGD, 3 HGD), t 5 1 (18 MET, 3 LGD) and t 5 2 (8 MET, 2 LGD) were not statistically different (Fig. 2b), despite histologic downgrading of dysplasia after therapy.…”
Section: Resultsmentioning
confidence: 93%
“…36 Although the latter is clear for patients with HGD, patients with MET and LGD also appear to have an increased risk. 4 We investigated 80 samples of BE before and after ablation by ALA-PDT or APC for LOH at tumor suppressor loci known to be involved in malignant progression in BE, i.e., the APC gene on 5q, P16 on 9p, the P53 gene on 17p and DCC and SMAD4 on 18q. Before treatment, frequency patterns of loss were observed that were in agreement with previously published reports, e.g., frequent LOH at the P16 locus starting already in metaplasia without dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several previous studies stated that patients with SSBE may develop dysplasia (Sharma et al, 1997) and EAC (Rudolph et al, 2000), some prospective studies have shown an increased risk of EAC development only in patients with LSBE (Weston et al, 1997;Hirota et al, 1999;Hage et al, 2004). Rudolph et al (2000) demonstrated that segment length was not related to cancer risk in a prospective cohort study of 309 Barrett's patients followed in the Seattle Barrett's Esophagus Project (P>0.2); however, when patients with HGD at entrance were excluded, a strong trend was observed, with a 5 cm difference in length associated with a 1.7-fold increase in cancer risk (95% confidence interval, 0.8-to 3.8-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Hirota et al (1999) reported that the prevalence of dysplasia and cancer differed significantly in patients with SSBE vs patients with LSBE in a comprehensive prospective study of 889 consecutive patients. More recently, Hage et al (2004) reported a significantly increased risk of progression to HGD or EAC with LSBE after a mean follow-up of 12.7 years. Thus, it is likely that length of Barrett's epithelium is an important risk factor for both the prevalence of concurrent dysplasia and cancer and the incidence of future malignant progression.…”
Section: Discussionmentioning
confidence: 99%